IbM Bilik Sterilisasi Dengan Cairan Disinfektan Berbahan Alami Daun Sirih Di Kecamatan Matan Hilir Selatan Kabupaten Ketapang - Aqla, Syarifah; Firman, Firman; Sartika, Sartika; Herman, Herman; Indra Septiansyah, Sy; Herkan Afandi, Idris; Santi, Maya; Azmi, Noprizan; Mastura, Syarifah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Mining Engineering as one of the D3 Study Programs at Politeknik Negeri Ketapang seeks to assist the government in preventing the spread of Covid-19 in Ketapang Regency. Through PKM activities in 2020, Mining Engineering provides an alternative to preventing the Covid-19 virus by making a natural disinfectant made from betel leaf and applied in sterilization booths. The sterilization booth with natural disinfectant liquid of betel leaf was given to one of the mosques in Ketapang Regency, Al-Muhdi Mosque, Pelang District, Ketapang Regency on Friday, July 10, 2020. It is hoped that this sterilization booth will make the surrounding community, especially the Al-Muhdi mosque congregation feel calm and comfortable during worship